Environmental perception of consumers of organic products: the case of agroecological fair of the Associação Cristã de Base (ACB), in the municipality of Crato (Ceará) - Pinheiro, Valéria Feitosa; Nascimento, Guilherme Silva; Alves, Christiane Luci Bezerra; Rodrigues, Anderson da Silva; Batista, Maria Larissa Bezerra (Universidade Federal Rural do Rio de Janeiro, 2020)
The current study presents a research about the environmental perception of organic food consumers from an agro-ecological fair supported by Associação Cristã de Base (ACB) in Crato’s city, southern Ceará state, northeastern Brazil. The methodological approach adopted regards to an analysis exploratory-descriptive based on data collected through primary research, through the application of a semi-structured questionnaire. For this reason, an Environmental Perception Assessment Index (IAPA) was calculated and structured by three dimensions: General Perception and Environment Relative Social Customs (PGCSRA); Perception of Habitual Consumption (PRCH); Perception Relating to Organic Food Consumption (PRCAO). Thus, Iapa’s general results indicates a high level of environmental perception related to the organic product’s consumption. Therefore, it can be concluded that the level of educational instruction, social interaction and the concern for future generations presented by these consumers are extremely important factors for the high values obtained in the index.